Pengaruh Senam Kegel Exercise Dalam Proses Pemulihan Ibu Nifas Dengan Persalinan Normal Diklinik Rismala Kecamatan Kisaran Barat - Jahriani, Nani; Sitorus , Ririn Anggriani (Cattleya Darmaya Fortuna, 2022)
During pregnancy, attention should be paid to breasts, especially breast hygiene and the shape of the nipples being flat or inverted. Such nipples are actually not an obstacle for mothers to breastfeed well by knowing that from the start, mothers have time to make efforts to make the nipples easier when breastfeeding. Apart from that, it is also very important to pay attention to hygiene issues (Rustarmadji, 2018).Research objectives: The general objective of this research is to determine the level of knowledge of mothers regarding breast care during pregnancy.This research method is descriptive research using a cross-sectional method. The population was 40 pregnant women at the Armiyanti Kisaran Clinic, sampling was carried out using total sampling with a total sample of 40 respondents. Data collection uses primary data with observation instruments. Analysis uses univariate and bivariate. Results: The results from 40 respondents can be concluded that 22 people had good knowledge (55.0%), 11 people had good knowledge (27.5%) and 7 people had less knowledge (17.5%). Conclusion: It can be seen that the level of knowledge of breast care in pregnant women is based on education, age, occupation, etc